Hedging opportunities for feeder pig finishers - Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the frequency of profitable, short, hedging opportunities that have been available to feeder pig finishers in recent years. The results indicate that there have been periods offering frequent opportunities to "lock in" a profit by hedging. However, there have not been many extended periods beyond 6 mo offering frequent profitable hedging opportunities, and over several feeding periods, no trading day offered profitable hedging opportunities. Though not always offering a profit, the futures market offered some improved returns relative to the cash market. During a few feeding periods, improved return opportunities were present in excess of 80% of the trading days, but overall, the frequency of improved returns was fairly low.
Keywords: Swine; Hedging; Hog marketing; Hog profits